Trait‐based community assembly of aquatic macrophytes along a water depth gradient in a freshwater lake. (16th September 2014) - Fu, Hui; Zhong, Jiayou; Yuan, Guixiang; Xie, Ping; Guo, Longgen; Zhang, Xiaolin; Xu, Jun; Li, Zhongqianng; Li, Wei; Zhang, Meng; Cao, Te; Ni, Leyi
Summary Trait‐based approaches provide a framework for integrating the distribution of functional traits associated with ecological strategies into the responses of plant community dynamics along environmental gradients. We used a trait‐based approach to unravel the processes governing macrophyte community assembly along a water depth gradient. We sampled 42 plots and 1513 individual plants and measured 12 functional traits and abundance of 17 macrophyte species. The results showed significant evidences of habitat filtering (i.e. a significant reduction in the range and variance of trait values) and of niche differentiation (i.e. trait values distributed more evenly than expected), both of which affected the functional responses of macrophyte communities associated with different sets of traits in significant different patterns along the gradient. Habitat filtering effects increased significantly for specific leaf area and leaf carbon content along the gradient. Niche differentiation effects increased significantly for leaf dry mass content, but decreased for ramet size, shoot height and leaf carbon content with increasing water depth, implying that the relative strength of biotic competition in a specific functional niche would vary with water depth. Intraspecific trait variability promoted significantly the detection of habitat filtering effects on stem diameter, lamina thickness and stem dry mass content, and niche differentiation effects on specific leaf area, leaf dry mass content, shoot height, stem diameter, stem dry mass content and ramet size. Community assembly processes shape the functional trait distribution within communities along environmental gradients through hierarchical effects of habitat filtering and niche differentiation. Our study highlights that niche differentiation plays a structuring role in macrophyte community assembly and that intraspecific trait variability is an important factor influencing macrophyte community dynamics.